Pelatihan Implementasi Kurikulum Merdeka (IKM) Bagi Guru Madrasah di Madrasah Ibtidaiyah Nurul Qur’an Pagutan Mataram: Independent Curriculum Implementation (IKM) Training for Madrasah Teachers at MI Nurul Qur'an Pagutan Mataram - Nasarudin, Nasarudin; Husnan, Husnan; Nurjannah, Nurjannah (EDUPEDIA Publisher, 2023)
Madrasah Ibtidaiyah Nurul Qur'an Pagutan which began implementing the independent curriculum in the 2022/2023 academic year in grades 1,2,3, and 5. MI Nurul Qur'an chose the independent option of sharing in implementing IKM by developing its own tools. MI Nurul Qur'an in preparing its teaching staff for IKM sent teachers to attend IKM training, but most of it was done bravely, so that the understanding of teachers was still limited, especially in making independent curriculum tools such as teaching modules to replace lesson plans. The purpose of the activity is to increase the understanding of madrasa teachers in implementing the independent curriculum, through seminars and interactive discussions which will be held on August 31, 2023. The implementation of this activity consists of three stages, namely preparation, seminar activities, and closing and follow-up. Madrasah teachers feel that their understanding of the independent curriculum policy is increasing, and wish to be assisted in creating independent curriculum tools.